EFFECT OF SOWING ENVIRONMENT AND NITROGEN LEVELS ON LIGHT INTERCEPTION AND ITS EFFICIENCY IN DRY MATTER PRODUCTION IN WHEAT CULTIVARS - NIWAS, RAM; Singh, MOHINDER; KHICHAR, M.L. (Annals of Agricultural Research, 2014)
The field experiments were conducted at research farm of the Department of Agricultural Meteorology, CCS Haryana Agricultural University, Hisar. Five wheat cultivars : WH 542, PBW 343, UP 2338 Raj 3765 and Sonak were sown on 25th Novemeber, 10th and 25th December with four nitrogen levels viz., no nitrogen, 50, 100 and 150 per cent of recommended dose. Leaf area index, dry matter at anthesis and final dry biomass were measured at different growth stages. Photosynthetically active radiation was measured with line quantum sensor at different growth stages in all the treatments. Transmitted, refleced and absorbed photosynthetical active radiations were computed. Absorbed PAR in wheat decreased with delay in sowing. Wheat fertilized with 180 kg nitrogen/ha absorbed maximum photosynthetical active radiations. Delay in sowing adversely affected the radiation use efficiency of wheat crop. The cultivar PBW 343 was more efficient in radiation utilization in comparison with WH 542, UP 2338, Raj 3765 and Sonak. The maximum value of radiation use efficiency varied between 2.55 to 2.80 (1998-99) and 2.92 to 3.14 g/MJ (1999-2000). Radiation use efficiency explained around 65 per cent variability in leaf area index and dry biomass of wheat crop.